PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI PADA BAKARA CAFE & KITCHEN DEPOK - Anjar Priatama; Ria Arifianti; Raden Ratna Meisa Dai (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to determine and test the influence of product quality on purchasing intention at Bakara Cafe & Kitchen Depok. In this research, sampling used a non-probability sampling method with a purposive technique for Bakara consumers as respondents. The data used in this research uses primary and secondary data, namely questionnaires as primary data and observations as secondary data using quantitative methods. The results in this research obtained a significance value of 0.867 > 0.05 resulting from the correlation analysis test. Then the product quality variable has an influence of 74.9% on the purchase intention variable and the rest is influenced by other factors. Apart from that, the t value is 18,004 and the t table value is 1.982, so t count > t table or (18,004) > 1,982, meaning H0 can be rejected and H1 can be accepted or the hypothesis can be accepted with a significant influence between the product quality variable and the purchase intention variable.